FULL DAY SCHOOL DALAM PERSPEKTIF AL-QUR’AN (Telaah Surat Ar-Rahman dan Al-Jumu’ah) - Marwansyah Marwansyah; Ahmad Wahyu Hidayat (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
This study describes full day school in the perspective of the Koran (study of Surah Rahman and Al-Jumu'ah). This research uses library research with analytical study methods. Analytical studies used are content analytical and analytical descriptions of full day school policies. Educational success lies in the curriculum applied. The curriculum must be relevant to the needs of students and parental guidance. One indication that education in a school is successful is what is given to students as desired by the community or parents of students. If discussing the world of education today, certainly can not be separated with the term full day school. The Results of the Linkage of Surat Ar-Rahman and Surat Al-Jumu'ah with education, namely: An educator or teacher must prepare himself with the nature of rahman, which is to have compassion for all students or students indiscriminately, both for students who are smart, stupid , diligent, lazy, good or naughty, before the teacher is in front of students. The teacher must first prepare in terms of mastering, understanding the material that will be delivered to students, a teacher whatever the material he teaches should direct his students to become knowledgeable, civilized and dignified human beings that lead to devotion to the Almighty, a teacher whatever the lessons delivered , make it clear, to the point that a student truly understands. Do not let a student not really understand the material taught has moved to another material, With the sending of the apostle by Allah for mankind, aims to provide scientific education from the book and perfecting the morals and creeds, Education, teaching, and skills are forms of forms to develop the potential in oneself which is part of the task of an educator.